Botanical derivative in mosquito control programme to minimize pesticide pollution hazards - P. K. Mishra; Dheeraj Khatarkar; Shail Joshi (Environment Conservation Journal, 2006)
Alkaloid compound  has been  isolated from the P. ether chloroform , methanol and water  extract of the aerial part of the Lantana camara L. The compound demonstrated strong insecticidal activity against Culex quinaquifasciatus. the chemical derived from plants have been projected as weapons  in future  mosquito control programme  as  they shown  to toxic  growth and reproductive inhibitor .